Exploring the Perception of Adolescent Students on Self-Stigma towards Mental Health and Counseling - Pokharel, Rashika (Adhyayan Journal, 2025)
In my five years of experience as a psycho-social counselor, I have consistently observed significant stigma surrounding mental health and counseling among adolescents, often exacerbated by peer pressure and societal norms. Even in critical circumstances, counseling is routinely refused because of the prevailing stigma. Mindful of this experience, during my MEd in School Counseling studies at Kathmandu University, I conducted this research on self-stigma among adolescent using Social Identity Theory (SIT) and Self-Discrepancy Theory (SDT). I employed qualitative methods that involved in-depth interviews with four adolescent students of Mahendra Ratna Secondary School, and Mechi Multiple Campus, Jhapa, who were purposefully selected. In-depth interviews, and thematic analysis, providing verbatim accounts to highlight the influence of stigma were used to make the interpretations. My findings revealed that fear of social rejection among the adolescents and the need to maintain a strong public appearance contribute to reluctance in seeking help. Addressing self-stigma and incorporating mental health education into school curricula are imperative for improving access to mental health care.